Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
La plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2019)

Instantané de recherche : portrait de la santé mentale des Canadiens francophones en situation minoritaire - CAMH-Evidence Exchange Network (2020)

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.